2011
DOI: 10.1007/s10340-011-0372-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neem oil against thrips (Thysanoptera) on mango panicles and its compatibility with mango pollinators

Abstract: A field trial was conducted in a mango (Mangifera indica L.) orchard located on Penang Island, Malaysia, to determine the efficacy of neem oil at 1, 2 and 3% concentrations and imidacloprid, a commonly used synthetic insecticide, on populations of thrips and their toxicities to mango pollinators. Daily periodicities of several pollinators that frequently visited mango panicles were studied prior to the insecticide trial to determine the appropriate time of insecticide application. Pollinators were collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Even though it took five months of observation to show that biopesticides, especially the botanical pesticide, have the potential to control the Thrips. This data quite compatible with other research that stated neem, as one of the main ingredients of the botanical pesticide, can be a good alternative to synthetic insecticides to control Thrips in several crops like mango [18], cotton [19], cardamom [20], cowpea [21], and pummelo [22]. All three of the botanical pesticide ingredients (neem oil, citronella oil, and clove oil) are also stated by other research as potential biopesticides to control Spodoptera frugiperda [23] and fly species [24].…”
Section: The Intensity Of Thrips Attacksupporting
confidence: 92%
“…Even though it took five months of observation to show that biopesticides, especially the botanical pesticide, have the potential to control the Thrips. This data quite compatible with other research that stated neem, as one of the main ingredients of the botanical pesticide, can be a good alternative to synthetic insecticides to control Thrips in several crops like mango [18], cotton [19], cardamom [20], cowpea [21], and pummelo [22]. All three of the botanical pesticide ingredients (neem oil, citronella oil, and clove oil) are also stated by other research as potential biopesticides to control Spodoptera frugiperda [23] and fly species [24].…”
Section: The Intensity Of Thrips Attacksupporting
confidence: 92%
“…Detergent has a large non-polar hydrocarbon end and water-soluble polar end (Swarbrick, 2002). From the laboratory studies 0.3% spreader concentration (producing lowest height of oil film floating with highest grade) was selected for emulsification of 2.0% oil, further which was used for bioefficacy study (Aliakbarpour et al, 2011;Stanley et al, 2014;Sridharan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…There is likely shift in the bees' occurrence from treated plots as a result of botanical oils repellency. Aliakbarpour et al (2011) reported that 2.0% neem oil was effective and brought 59.8% reduction in thrips along with 24.9% mortality of pollinators and concluded that, proper timing of neem oil application such as, at midday when pollinators are least active would prove less detrimental to mango pollinators and at the same time can control thrips.…”
Section: Tmentioning
confidence: 99%
“…However, the constant use of these chemicals may cause selection of resistances to insecticides in agricultural pests, environmental pollution with negative side effects on human health and on non-target arthropods, which can ultimately leads to the disrupting of biological control (Desneux et al, 2007). Therefore, there has been increasing worldwide interest in the development of alternative and sustainable means for modern pest management strategies, including re-appraisal of plant derivate usage (Aliakbarpour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%